27 Contrast induced acute kidney injury – a five year review. (16th October 2019) - Burns, L; Kinnin, M; McEneaney, D; Menown, I; Kurth, M; Morgan, N; Harbinson, M; Connolly, M
Abstract : Introduction: Contrast induced acute kidney injury (CI-AKI), currently defined as a delta rise in serum creatinine of ≥26.5 µmol/litre or a relative rise of ≥50% from baseline measured at 48 hours following administration of iodinated contrast media, is reported to complicate almost 20% of studies in high-risk individuals1. As previously presented, we implemented a formalised protocol for the management of chronic kidney disease (CKD) patients in our cardiac catheterisation laboratory2–3. This included clear pre and post-hydration guidance, use of the Mehran score to identify high-risk patients, ensuring nephrotoxic medications were withheld and use of advice sheets for patients and GPs. With this we achieved an 8.9% reduction in the rates of CI-AKI for patients with CKD. This study highlights a five-year re-audit of CI-AKI rates. Methods: During the period between August 2018 and February 2019, a total of 2025 patients underwent contrast angiography ± percutaneous coronary intervention (PCI) at our institution. Of these, 266 (11.1%) had CKD. All patients with an estimated glomerular filtration rate (eGFR) ≤60 mls/min/m 2 presenting for coronary angiography at our laboratory were included. Data were obtained from lab reporting systems and from the Northern Ireland electronic care record. Demographics, risk factors and renal function before and at 48 hours post angiogram were recorded. Mehran scores were calculated for each patient and pre/post procedure intravenous fluids prescribed if appropriate. CI-AKI was defined as a delta rise in serum creatinine of ≥26.5 µmol/litre or relative rise of ≥50%. Case report forms were used to record blood results. Patients were telephoned at 48 hours and advised to restart withheld nephrotoxic medications if appropriate or, if necessary, given AKI advice with repeat blood sampling a further 48 hours later. Data were non-parametric on Shapiro-Wilk testing therefore Mann-Whitney U test (p<0.05 as significant) was applied for continuous variables. Chi squared test was applied for categorical variables (p<0.05 as significant). Results: Of the 266 patients identified, 22 (8.3%) developed CI-AKI 48 hours post-contrast. Using the previous definition of CI-AKI at the time of our initial study in 2014 (creatinine rise ≥25%), 11 patients (4.1%) developed CI-AKI which remains well below the published literature rate of 10–15%. Average Mehran scores were significantly higher in those patients that went on to develop CI-AKI compared with those that did not (14 vs. 10, p<0.001, table 1). Conclusion/Implications: Our comprehensive protocol for the peri-angiography management of CKD patients has achieved a significant reduction in the rates of CI-AKI at our institution, which has been sustained over a five-year period. There is a statistically significant correlation between higher Mehran score and development of CI-AKI, indicating the value of this tool as a surrogate marker for high-risk patients.